Theoretical prediction of a graphene-like 2D uranyl material with p-orbital antiferromagnetism. Issue 29 (6th June 2022) - Zhao, Xiao-Kun; Cao, Chang-Su; Liu, Jin-Cheng; Lu, Jun-Bo; Li, Jun; Hu, Han-Shi
Abstract : An unprecedented graphene-like 2D uranyl material with p-orbital antiferromagnetism is found to be stable by computational investigations. Abstract : Versatile graphene-like two-dimensional materials with s-, p- and d-block elements have aroused significant interest because of their extensive applications while there is a lack of such materials with f-block elements. Herein we report a unique one composed of the f-block element moiety of uranyl (UO2 2+ ) through a global-minimum structure search. Its geometry is found to be similar to that of graphene with a honeycomb-like hexagonal unit composed of six uranyl ligands, where each uranyl is bridged by two superoxido groups and a pair of hydroxyl ligands. All the uranium and bridging oxygen atoms form an extended planar 2D structure, which shows thermodynamic, kinetic and thermal stabilities due to σ/π bonding as well as electrostatic interactions between ligands. Each superoxido ligand has one unpaired (2pπ* ) 1 electron and is antiferromagnetically coupled through uranyl bridges with 2pπ* –5f δ –2pπ* superexchange interactions, forming a rare type of one-dimensional Heisenberg chain with p-orbital antiferromagnetism, which might become valuable for application in antiferromagnetic spintronics.